Dinamika Ekonomi-Bisnis Provinsi Jambi Di Era Pengetahuan Terbuka: Kajian Bibliometrik-Slr Terhadap Peta Riset Global Bereputasi Dan Implikasinya - Alfarizi, Muhammad; Widiharjanti, Isti (Jurnal Khazanah Intelektual, 2025)
n facing the global transition towards an open knowledge economy, Jambi Province encounters complex challenges such as digital inequality, agrarian governance issues, and the sustainability of its natural resource-based economy. This study aims to map the direction, trends, and research gaps in global literature related to regional economicbusiness dynamics relevant to the context of Jambi, as well as to evaluate their implications for evidence-based public policy formulation. Employing a Systematic Literature Review (SLR) and bibliometric approach, this study analyzed 123 Scopusindexed articles (2000–2025), following the PRISMA protocol and utilizing Bibliometrix and VOSviewer for analysis. The results reveal seven dominant thematic clusters, namely participatory governance, ecosystem sustainability, agribusiness value chains, agrarian conflicts, smallholder productivity, socio-ecological transformation, and consumer preferences for sustainable products. There is a notable gap in the literature concerning the integration of Jambi’s development strategies based on open information systems, digitalization of farmer cooperatives, and data-driven cross-sector policy approaches. Jambi's position in the global research landscape remains marginal, marked by low levels of international collaboration. This study recommends strengthening open research ecosystems, fostering triple helix partnerships, and developing regional economic policies supported by geospatial information systems. Keywords: Bibliometric, Jambi, Knowledge-Based Economy, Regional Sustainable Development